The efficacy and safety of neoadjuvant treatment with the PD-1 inhibitor for locally advanced colorectal cancer: a meta-analysis - Yu, Yan; Huang, Lin; Yan, Rong; Jiang, Min; Li, Shuang-Jiao; Fan, Wang-Dong (Frontiers in Oncology, 2024)
ObjectiveTo systematically evaluate the efficacy and safety of PD-1 inhibitors in neoadjuvant therapy for locally advanced colorectal cancer (LACRC).MethodRetrieved from PubMed, Embase, and the Cochrane Library, all relevant studies about PD-1 inhibitors for neoadjuvant treatment of LACRC were collected from inception to 31 December 2023. The efficacy was assessed by the rate of pathological complete response (PCR), clinical complete response (CCR), and major pathological response (MPR), and the safety was evaluated by the incidence of all adverse effects (TRAEs). Subgroup analysis was conducted by experimental design, types of PD-1 inhibitors, and disease types.ResultA total of 803 patients were included in 21 studies. The results of the meta-analysis showed that the PCR rate of PD-1 inhibitors in the treatment of LACRC was 54% (95% CI: 43%–65%, P<0.05); the CCR of anti-PD-1 was 40% (95% CI: 26%–54%, P<0.05); the MPR was 66% (95% CI: 56%–76%, P<0.05); and the irAEs was 27% (95% CI: 17%–37%, P<0.05). Subgroup analysis showed that the PCRs in prospective studies and retrospective studies were 49% (95% CI: 32%–66%, P<0.05) and 57% (95% CI: 42%–73%, P<0.05), respectively. Among the 803 patients, 619 (77%) were diagnosed with rectal cancer (RC), and the PCR and MPR were 49% and 65%, respectively; 184 (23%) were diagnosed with colorectal cancer (CRC), and the PCR and MPR were both 67%. In our meta-analysis, types of PD-1 inhibitors, including sintilimab, toripalimab, camrelizumab, avelumab, pembrolizumab, and tislelizumab, and patients who received PD-1 inhibitors alone or in combination achieved good PCR rates.ConclusionNeoadjuvant therapy combined with a PD-1 inhibitor has a favorable PCR and relatively low incidences of irAEs for patients with LACRC, suggesting that this regimen including a PD-1 inhibitor is significantly effective and sufficiently safe.